Do diálogo inter-religioso à construção da espiritualidade: uma análise de procedimentos pedagógicos em aulas de ensino religioso - Nascimento, Valmir Pontes do (2014)
The goal of this paper is to reflect about the otherness and inter-religious dialog which are present in interactions as foundations for pedagogical procedures in Religious Education classes (ER), in interfaces with public policies related to this curricular component and in interlocutions with different authors about dialogism in education. Dialogic pedagogy is examined in connection with the dynamic of religious expressions, specifically the Brazilian ones, and seeking to understand how educators can gain pedagogical benefits from these manifestations of spirituality in the school space, in Religious Education (ER). The conceptual foci verified in the bibliographic research are made in an integrated way and in connection with the results of a field research carried out in a school of the private network of the metropolitan region of Porto Alegre RS. In the first chapter the results of the empirical research are presented, which verify a methodology of teaching based on otherness and on interaction and its implications on the construction of the spirituality of the student. In the second chapter the reflection is on religion and post-modernity, seeking to understand what being religious means in this social context. The plural religious scenario is observed, religious diversity and mobility are identified and the inter-religious dialog in its perspectives and possibilities, specifically in Brazil, is examined. In the third chapter, the discourse is about Religious Education in the face of this multifaceted and complex current context, observing the plural school reality. Concepts of interaction, otherness and spirituality are sought, presenting perspectives of a dialogic pedagogy. ER is studied in its historic process, in Brazil, and analyzed in pedagogical-epistemological terms, thus examining dialogic pedagogy in its possibilities of application in this curricular component, in its current configuration.